2012
DOI: 10.1177/0093854812458095
|View full text |Cite
|
Sign up to set email alerts
|

Intervention With Problem Officers

Abstract: Police executives have increasingly assumed-or they have been compelled to accept-responsibility for managing the risk of misconduct by their officers through the implementation of early intervention (EI) systems, even though social science has provided very little evidence on their effectiveness, or on their unintended effects. We examine the effects of one police agency's EI system intervention, the Officer-Civilian Interaction (OCI) School, on indicators of risk-related outcomespersonnel complaints, citizen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…An EI system provides supervisors and managers the opportunity to address problematic officer behavior in a positive and productive way (Bouche et al, 2016;Stephens, 2011). EI systems are data-driven; they track performance indicators and identify at-risk officers based on certain thresholds, which can trigger an intervention with the officer and postintervention monitoring by the supervisor (Walker et al, 2005;Worden et al, 2013). An EI system alerts an agency when a performance indicator or combination of performance indicators meets a certain threshold, such as a specific number of complaints in a certain time frame.…”
Section: Early Intervention System Design and Implementationmentioning
confidence: 99%
See 4 more Smart Citations
“…An EI system provides supervisors and managers the opportunity to address problematic officer behavior in a positive and productive way (Bouche et al, 2016;Stephens, 2011). EI systems are data-driven; they track performance indicators and identify at-risk officers based on certain thresholds, which can trigger an intervention with the officer and postintervention monitoring by the supervisor (Walker et al, 2005;Worden et al, 2013). An EI system alerts an agency when a performance indicator or combination of performance indicators meets a certain threshold, such as a specific number of complaints in a certain time frame.…”
Section: Early Intervention System Design and Implementationmentioning
confidence: 99%
“…Of these, findings are generally positive but mixed, and most have been limited to individual agencies (e.g. Charette, 1994;Walker et al, 2001;Worden et al, 2013). Despite this variation in results, most studies have found that EI systems have a positive effect on officer misconduct and accountability.…”
Section: Previous Empirical Researchmentioning
confidence: 99%
See 3 more Smart Citations